Pollen morphology: a source of information for taxonomic studies within Campomanesia (Myrtaceae). (2nd January 2023) - Luber, Jaquelini; Carrijo, Tatiana Tavares; Martins, Mauricio Moreira; Mendonça, Cláudia Barbieri Ferreira; Gonçalves-Esteves, Vania
Abstract: Campomanesia is a well-delimited Neotropical genus of Myrtaceae, but some of its species have a poorly understood circumscription. Pollen morphology can provide characters to clarify the relationships among such taxa. Here, we analyze the pollen grains of 16 species of Campomanesia using light and scanning electron microscopy. Heat map and multivariate regression tree analyses were performed aiming to detect differences among species based on pollen morphology. Pollen grains of the studied taxa are isopolar monads that are oblate or, less often, suboblate, 3(4)-colporate, syncolporate or parasyncolporate, with a triangular or quandrangular amb. The exine ornamentation varies among rugulate-granulate, granulate, rugulate and rugulate-espiculate. Fastigium is present in 14 species, and a costa is present in three species. The heat map and regression tree analyses based on 16 character states of pollen morphology were able to distinguish all species of Campomanesia studied here. Some species differ from all the other species, such as Campomanesia guaviroba due to its exclusively rugulate exine. Amb, shape and exine ornamentation were distinctive characters, as previously reported for other genera of Myrtaceae. However, the presence of fastigium also proved to be an informative pollen character for species distinction in Campomanesia . Based on the sample of this study, we can state that Campomanesia is a eurypalynous genus within Myrtaceae.